Hospitality and community after Christendom - Francis, Andrew (After Christendom series, 2012)
This book aims to show how nurturing hospitality in the "discipleship community" leads to growth. It seeks to re-examine the challenge, biblically and in radical Christian movements, presented by the pre-Christendom church in its patterns of hospitality and community to so 're-work' these to be more effective in mission, personally and corporately, after Christendom. The book re-examines Jesus' intentions, the wider biblical material, and congregational practices of sharing Communion as well as drawing on radical church history to demonstrate that despite increasing marginalization, hospitality and community are essential to the church's nature, well-being and mission. It goes on to use many practical examples, as well as leadership strategies to enable congregations to restore hospitality and community to its necessary place. It also provides an accessible theology as well as some original liturgies to underpin Christian life as we move forward after Christendom. --